Summary of Results of the 2006-2007: Study of Faculty Attrition at UW-Madison - Maidl Pribbenow, Christine (My University, 2008)
In the spring semester of 2007, Vice Provost Laurie Beth Clark approached the WISELI staff about conducting a research study of faculty attrition at UW-Madison. This request came on the heels of a report disseminated in 2006 about why female faculty in scientific and engineering fields leave campus.i Using similar methodology, the following describes a study of both female and male faculty members from across campus who left between the fall of 2006 and summer of 2007.
Keywords: Faculty and Staff Academic Affairs